Customer Satisfaction at Artshop Made: Exploring the Impact of Promotional Mix, Product Quality, and Store Atmosphere - Putu Tania Wijayanti; Ni Luh Nurkariani; Laura Laura (International Journal of Economics Development Research (IJEDR), 2023)
Customer satisfaction is something that business owners feel is critical to the success of their company. Because satisfied customers will act positively on the business by remaining loyal, making additional purchases, and recommending it to others. The purpose of this research is to find out how the promotion mix, product quality, and the Artshop Made store environment affect customer satisfaction. All Artshop Made customers are used as the research sample population. 50 people randomly selected for the study sample constituted the total. The information used in this study was collected from survey responses and tested using multiple linear regression analysis techniques. The findings of this study show that the promotion mix has a positive and significant effect on customer satisfaction. Customer satisfaction is greatly influenced in a beneficial way by product quality. Customer satisfaction is positively and significantly influenced by the store environment. In the future Artshop Made is expected to be able to improve the Promotion Mix, Product Quality and Store Atmosphere in order to create customer satisfaction.